STORAGE TECHNIQUES OF CEMPAKA WASIAN (Magnolia tsiampaca (Miq.) Dandy) SEEDS - Arif Irawan; Hanif Nurul Hidayah; Julianus Kinho; Jafred E. Halawane (Indonesian Journal of Forestry Research, 2020)
Cempaka wasian is a type of woody tree which has a substantial historical value associated with the local culture of the Minahasan people. The improvement of cempaka wasian plantation is essential due to their enormous importance and usage. This study aims to discover the impacts of duration, storage room, and containers used for the appropriate storage of cempaka wasian seeds. The design used in this study is entirely randomized design organized with a factorial pattern which consists of 3 factors; 1) storage duration, 2) storage room and 3) storage containers. Duration of storage was 2, 3, 4, and 5 months; meanwhile, storage rooms comprised of refrigerators, chambers, and air-conditioned room. Moreover, storing containers consisted of calico cloth, aluminium foils, and plastic bags. The study finding indicates that the seeds of cempaka wasian could still germinate if stored for five months by using plastics bags inside refrigerators. A significant provision of seeds and suitable timing are closely related to the proper seed storage techniques.